The Scripture on Tiles: Dutch Tiles as an Example of the Biblical Culture of Everyday in the Republic - Oczko, Piotr (Werkwinkel, 2015)
The history of Dutch tiles started in the sixteenth century Antwerp in the workshops of the Italian potters who had settled in the city upon the Scheldt. Due to the political and social factors (i.e. huge wave of refugees during the Dutch Revolt), tile production was moved to the Northern Netherlands, where it was fully developed and the offer of the Republic’s tile works began to enjoy greatest fame and a huge commercial success all over Europe. The given article deals mostly with Dutch tiles representing the biblical scenes (bijbeltegels) and discusses their numerous contexts, such as confessional and social background, iconographical origin of their designs (engravings, illustrated Bibles, stencils), the taste and status of the potential buyers. Moreover, the artistic and cultural phenomenon of Dutch biblical tiles has been interpreted in terms of a much wider tradition, namely the ‘biblicisation’ of everyday life in the Dutch Republic and its interiors. Finally, the issue of Dutch tiles, being the symbols of the national cultural tradition, has been brought up.